REFUGEE STATUS IN MODERN TIMES - Tukhtasinov Shokhrukhhon Ne’matjon o’g’li (Scholar Express Journals, 2023)
This article discusses the international protection of refugees, those in charge of their protection. This article describes the problems that arise in the process of protection and their solutions
Keywords: Refugee; United Nations High Commissioner for Refugees; voluntary repatriation